Trifocal Lenses for Cataract Surgery - Daniel H. Scorsetti (The Ophthalmology, 2017)
Since the introduction of the first intraocular lens in 1949, many technological advances have been made in order to optimize its design and construction. Owing to a number of recent advances and developement of modern lenses, it has now become possible to not only correct post-operative aphakia but also provide good visual acuity for far, intermediate and near distances by decreasing or eliminating eye glasses or contact lenses in majority of cases. Apart from the above, modern intraocular lenses also reduce eye aberrations and protect the retina from ultraviolet (UV) radiation and the toxicity of blue light that are important factors to be taken care of in visual health.